Utilização da combinação da reatividade de anticorpos da classe IgG, subclasses IgG 1 e IgG 2 para definição de diagnóstico diferencial entre as infecções por Trypanosoma cruzi e Leishmania spp - Selva, Ana Flavia Ferreira (2022)
Chagas disease (CD) is a chronic infectious disease, considered an anthropozoonosis that represents a major public health problem and mandatory notification, with a high level of morbidity and mortality occurring throughout Latin America. Caused by a protozoan that belongs to the Trypanosomatidae family and the Trypanosoma genus, Trypanosoma species (Schizotrypanum) cruzi.CD can be transmitted in several ways, the most common being vector, through the bite of a hematophagous insect of the Reduviidae family, with the species Triatoma infestans being popularly known as “barber”, in Brazil, the main responsible for causing the disease in cycle domiciliary, being able to transmit the disease to their vertebrate hosts, which are several species of mammals, being man (accidental) and dog (main reservoir of the disease) the main hosts and to their invertebrate hosts such as triatomines. Once infected, the individual may present in the acute phase of the disease the sign of chagoma and the sign of pomegranate, accompanied by some clinical signs such as fever and inappetence. In the chronic phase, the disease can manifest itself in an indeterminate, cardiac, digestive, neurological or mixed form (more rare). As for their diagnosis, they can be made by different methods, parasitological, serological and molecular. Serological methods are the most used, due to the low parasitic load in the chronic phase, limiting the parasitological. Two serological tests are always recommended, due to their low specificity, and cross-reactions with other parasites of the same family such as Leishmania spp may occur, due to the low sensitivity and specificity of some tests, this project aimed to define using the profile of immunoglobulin subclasses ( Total IgG, IgG1 and IgG2) by enzyme-linked immunosorbent assay (ELISA) is a way of differentiating between T. cruzi and the genus Leishmania, which is the main cause of serological cross reactions in the state of Espírito Santo for CD, through a low-cost method and that it can be used routinely in diagnostic centers.